(3YbhO GddBdi HTQM HOA GdCeGdjs - (3YHO Gddg Hf Ydj GdOedjLi GdCRHcGhi (B( (3GdCRHci (B) (3GdTGaYj GdedbH HShOjGfs; (3Ydj Hf YKeGf Hf SdjeGf Hf eMeO GdJjej GdGhSj (B((3GdGhTj(B) (3GdaQZGfj GdMfaj, CHh GdMSf SQGL GdOjf CHh eMeO GdGhTj,J (B569 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMi GdbOjQ CeG HYO gPG TQM dWja Ydi eJf HOGA GdCeGdi ai Yde GdJhMjO GNJUQJg ef TQhMgG GdeWhdI hGdeNJUQI jbhd eTJb ef Gdbhd hgh GddaX GdehVhY s
(3BNQgG (B:s
(3gPG GdfXe jSJYjf Hg GdWdHg Ydi age CUhd GdOjf GdMOjK ef OYG dCNjg HXgQ bGdJ GdedGFcI dg hddg eKd Pdc hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf (B" s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bUjOI jbhd GdYHO (B" (3GfXQ cTa GdXfhf L(B2 (3U` (B1349 (3JhMjOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B475s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs